Acute effects of long-lasting stretching and strength training on maximal strength and flexibility in the calf muscle - Warneke, K.; Wohlann, T.; Lohmann, L.H.; Schiemann, S. (German Journal of Exercise and Sport Research, 2023)
The so-called "stretch-induced force deficit" is known from a large amount of research. There are many theories trying to explain the stretch-induced force deficit and increases in the range of motion (ROM) which all offer a stretch training-specific explanation. However, when performing a commonly used strength training session, a reduced maximum strength (MSt) capacity can be assumed as well. Based on this, the aim of the study is to investigate the tension-induced force deficit due to a suprathreshold strength or stretching training stimulus. Therefore, 71 participants (age: 24.1± 4.2 years, height: 176.3± 5.7cm, weight: 74.1± 7.5kg) were divided into three groups: static stretching group (SST), strength training group (STR), and control group (CG). To investigate possible mechanical tension-induced force deficits, SST performed a long-lasting static stretching intervention for 1h using an orthosis, while STR executed a common strength training intervention (5× 12 repetition) for the plantar flexors. The results show a significant reduction of measured MSt as well as increased ROM for both SST and STR following the interventions. Consequently, we found similar acute effects of stretching and strength training regarding MSt and flexibility. We conclude that the decreased MSt capacities can possibly be attributed to mechanical tension-induced damage of the muscle that is not linked to a specific training method. The improvements in flexibility found in both intervention groups might be attributed to warm up effects when inducing high mechanical tension to large ankle joint angles.